Patient-centred assessment and management of pain for older adults with dementia in care home and acute settings. Issue 2 (20th February 2014) - Newton, P; Reeves, R; West, E; Schofield, P
Summary: Evidence suggests that there is a greater prevalence of pain, particularly chronic pain, in the older than in the younger population. This review looks at how dementia affects older people's ability to report pain, and indicates that pain is poorly assessed and managed in people living with dementia, in particular in care and acute settings. The review also reports findings from two recent studies looking at ways of improving the assessment and management of pain in acute settings. Multi-dimensional, patient-centred approaches to assessing and managing pain in those living with dementia are required, and future research should focus on innovative and practical approaches that can be applied in care home and acute settings.